(untitled) (The Review of Diabetic Studies, 2025)
This research examines the integration of public health principles and family medicine practice in Saudi Arabia, presenting a framework for community-based preventive care that aligns with Vision 2030 healthcare transformation goals. Using a mixed-methods approach combining quantitative analysis of health data from major Saudi healthcare institutions and qualitative insights from healthcare professionals across five specialties (General Practitioner, Health Specialist, Family Medicine Physician, Physical Therapy Specialist, and Obstetrics & Gynecology, Paramedics & Nursing Specialist), this study proposes a novel model for preventive healthcare delivery. Our findings reveal significant opportunities for leveraging collaborative approaches to enhance disease surveillance, optimize healthcare resource allocation, and develop targeted interventions for priority health conditions in Saudi Arabia. The research identifies four key pillars for successful integration: standardized preventive care protocols, cross-disciplinary collaboration mechanisms, patient-centered implementation frameworks, and sustainable knowledge transfer systems. This paper contributes to the evolving discourse on preventive healthcare in Saudi Arabia by demonstrating how synergies between public health and family medicine can serve as catalysts for advancing community-based preventive care capabilities in alignment with Vision 2030 healthcare transformation goals.